Internal Control Environment for Fraud Detection and Prevention: Lingkungan Pengendalian Internal dalam Deteksi dan Pencegahan Fraud - Aisha Hanif; Binti Nadhifah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Internal control is considered a key factor in maintaining organizational integrity and preventing fraud within higher education institutions. Specific background: Previous studies mostly examined internal control in business organizations, leaving higher education practices less explored. Gap: Limited qualitative evidence explains how control environments work in educational settings. Aims: This study aims to identify the effectiveness of the internal control environment in preventing fraud at a private university in Indonesia. Results: Qualitative data collected through interviews and processed using NVivo show that several control components have been implemented, yet certain elements still require improvement such as monitoring and delegation. Novelty: The study presents empirical insight based on direct campus practices, revealing the contextual role of internal control in academic institutions. Implication: The findings suggest that strengthening internal monitoring and ethical culture is essential to reduce fraud risks in universities. Highlights:• Internal control environment in higher education• Fraud prevention mechanisms• Empirical qualitative evidence Keywords: Internal Control, Fraud, Higher Education, Audit, COSO